Dry sliding tribological properties of self-mated couples of B4C-hBN ceramic composites. Issue 1 (January 2017) - Li, Xiuqing; Gao, Yimin; Wei, Shizhong; Yang, Qingxia; Zhong, Zhichao
Abstract: In this paper, dry sliding tribological properties of self-mated couples of B4 C-hBN ceramic composites containing different amounts of hBN have been evaluated using a pin-on-disc friction and wear machine, and the worn surfaces of B4 C-hBN specimens have been observed and analyzed by scanning electron microscope (SEM). It is found that the dry sliding tribological properties of self-mated couples of B4 C-hBN ceramic composites take on obvious regularity: with hBN content increasing, the friction coefficient gradually decreases, but the wear coefficient gradually increases. The decrease of friction coefficient could be largely attributed to the formation of a transfer film formed on the wearing surface of the B4 C-hBN specimens. The formation of the film is investigated.